Locally advanced cancer of the tongue base: new method of surgical treatment - I. A. Zaderenko; A. M. Mudunov; S. Yu. Ivanov; R. I. Azizyan; A. A. Akhundov; S. B. Alieva; V. T. Tsiklauri; M. N. Narimanov; A. E. Kazimov; K. D. Il’kaev; A. V. Khromushina (Опухоли головы и шеи)
Introduction. Patients are characterized by locally advanced tumors in 70–80 % of cases at presentation, so possibility of cure and surgical treatment is limited. Total glossectomy, tongue base resection is associated with severe and permanent disability. Such surgical procedures lead to severe dysphagia, alalia and social maladjustment. Enumerated issues motivated us to develop new method of surgical treatment  of locally advanced base of tongue cancer.Objective is to introduce new opportunities of surgical treatment of locally advanced cancer of the tongue base.Materials and methods. Glossectomy is accomplished in 5 patients suffering from tongue cancer and admitted to N.N. Blokhin National Medical Research Center of Oncology. Swallowing and speech is preserved in all 5 cases.Results. The main advantage of the proposed method is that the cut out muscle flap has a different innervation from different cranial nerves involved in the rate of swallowing, so there is not just a mechanical movement of the epiglottis, but also the control of swallowing by the central nervous system. The reduction of injury and operation time in the proposed method is due to the fact that tissues directly contacting with the defect are used to preserve swallowing and speech. The proposed muscle flap has various sources of blood supply, which improves its nutrition and reduces the risk of complications, and healing occurs in a shorter time in comparison with the prototype. All of the above reduces the duration of hospitalization for an average of 7–9 days.Conclusion. The developed surgical technique allows to achieve early rehabilitation; patients are able to breathe effortlessly, swallow and speak. There is no need in permanent tracheostoma and percutaneous endoscopic gastrostomy tube. All patients remains socially active.